Environmental health ethics - Resnik, David B. (Cambridge University Press, 2012)
Environmental Health Ethics illuminates the conflicts between protecting the environment and promoting human health. In this study, David B. Resnik develops a method for making ethical decisions on environmental health issues. He applies this method to various issues, including pesticide use, antibiotic resistance, nutrition policy, vegetarianism, urban development, occupational safety, disaster preparedness, and global climate change. Resnik provides readers with the scientific and technical background necessary to understand these issues. He explains that environmental health controversies cannot simply be reduced to humanity versus environment and explores the ways in which human values and concerns, health, economic development, rights, and justice interact with environmental protection"--Provided by publisher